KUALITAS VERSUS STANDAR - Arfan Bakhtiar (TEKNIK, 2008)
This paper discusses about standard and quality and the relation between those variables. The resultdescribes the strong relationship and contribution to the product successfulness in the trade and business.Based on the literature reviewed, it is clear that company products (goods and services) are basicallycompetitive if the product refered to designated standard. Standard automatically assures the quality of theproduct in the business trade